Hypereosinophilic syndrome associated with ulcerative colitis presenting with recurrent Loeffler's endocarditis and left ventricular thrombus treated successfully with immune suppressive therapy and anticoagulation. (5th September 2013) - Koneru, Srikanth; Koshy, George; Sharp, Colin; Khalafallah, Alhossain A
Abstract : We reported a case of a 28-year-old Caucasian woman with hypereosinophilic syndrome (HES) associated with ulcerative colitis who presented on separate occasions with Loeffler's endocarditis. She was admitted in 2008 with fever, headache, confusion and visual loss. Diagnostic workup uncovered an eosinophilia of 3.1×10 9 /L and major ECG abnormalities. Subsequent echocardiography revealed left ventricular wall motion abnormalities with mural thrombus. MRI brain scan showed multiple white matter lesions consistent with acute infarcts. She recovered rapidly with corticosteroids and anticoagulation. Four years later she re-presented with headache, fatigue and an eosinophilia of 13.4×10 9 /L. This occurred 3 months after cessation of immunosuppression and within 12 months of total colectomy for fulminant ulcerative colitis. Echocardiography was suggestive of hypereosinophilic endomyocardial fibrosis with left ventricular thrombus. Anticoagulation and corticosteroids were resumed with good effect. This report highlights the findings, treatment and outcome of ulcerative colitis-associated HES manifesting as recurrent Loeffler's endocarditis.